2020
DOI: 10.1097/rlu.0000000000002841
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative Perfusion and Function Parameters of Gated-SPECT Myocardial Perfusion Imaging in Patients With Concordant and Discordant Left Bundle-Branch Block

Abstract: Background Patients with left bundle-branch block (LBBB) can be classified to discordant LBBB (dLBBB) and concordant LBBB (cLBBB) according to T-wave orientation in lateral leads. This classification indicates different functional left ventricular (LV) parameters with worse prognosis in dLBBB patients. However, there are no data regarding the impact of this classification on perfusion status of the left ventricle. The aim of this study is to evaluate and compare the SPECT myocardial perfusion imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Although many studies have suggested a positive relationship between serum leptin level and risk of CAD, there are also studies that revealed controversial results. A study by Rahmani et al reported that there was a direct relationship between serum levels of leptin and the number of involved vessels in patients that underwent coronary angiography compared to controls [18]. However, Sattar et al [20] conducted a large prospective study in British men and revealed a moderate but NS correlation between serum leptin level and incident CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have suggested a positive relationship between serum leptin level and risk of CAD, there are also studies that revealed controversial results. A study by Rahmani et al reported that there was a direct relationship between serum levels of leptin and the number of involved vessels in patients that underwent coronary angiography compared to controls [18]. However, Sattar et al [20] conducted a large prospective study in British men and revealed a moderate but NS correlation between serum leptin level and incident CAD.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rahmani et al . reported that there was a direct relationship between serum levels of leptin and the number of involved vessels in patients that underwent coronary angiography compared to controls [18]. However, Sattar et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation